Biological Fixed Film. (1st October 2014) - Islam, Md. Shahinoor; Tumpa, Fahmida; Xue, Jinkai; Huang, Chunkai; Sharma, Kusumakar; Shi, Yijing; Liu, Yang
Abstract : Literature published during the year 2013 regarding the use of biofilms and bioreactors to treat water and wastewater is revie\ ed herein. The review is organized into the following sections: biofilm fornl. ationand factors Ulat impact biofilm fom13tion; xtracellular polymeric substance and its e rtraction from biofihns; biofilm consortia and quorum sensing; biofilm imaging teclmiques; biofilm carriers and biofilm reactors.